Nutrient Sensing via Gut in Drosophila melanogaster. - Chopra, G.; Kaushik, S.; Kain, P. (International journal of molecular sciences, 2022)
Nutrient-sensing mechanisms in animals' sense available nutrients to generate a physiological regulatory response involving absorption, digestion, and regulation of food intake and to maintain glucose and energy homeostasis. During nutrient sensing via the gastrointestinal tract, nutrients interact with receptors on the enteroendocrine cells in the gut, which in return respond by secreting various hormones. Sensing of nutrients by the gut plays a critical role in transmitting food-related signals to the brain and other tissues informing the composition of ingested food to digestive processes. These signals modulate feeding behaviors, food intake, metabolism, insulin secretion, and energy balance. The increasing significance of fly genetics with the availability of a vast toolbox for studying physiological function, expression of chemosensory receptors, and monitoring the gene expression in specific cells of the intestine makes the fly gut the most useful tissue for studying the nutrient-sensing mechanisms. In this review, we emphasize on the role of Drosophila gut in nutrient-sensing to maintain metabolic homeostasis and gut-brain cross talk using endocrine and neuronal signaling pathways stimulated by internal state or the consumption of various dietary nutrients. Overall, this review will be useful in understanding the post-ingestive nutrient-sensing mechanisms having a physiological and pathological impact on health and diseases.